2017
DOI: 10.7567/jjap.56.090307
|View full text |Cite
|
Sign up to set email alerts
|

Design of compact surface optical coupler based on vertically curved silicon waveguide for high-numerical-aperture single-mode optical fiber

Abstract: A surface optical coupler based on a vertically curved Si waveguide was designed for coupling with high-numerical aperture single-mode optical fibers with a mode-field diameter of 5 µm. This coupler has a quite small device size, with a height of approximately 12 µm, achieved by introducing an effective spot-size converter configured with the combination of an extremely short Si exponential-inverse taper and a dome-structured SiO2 lens formed on the coupler top. The designed coupler shows high-efficiency optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The device fabricated using electron-beam (EB) lithography demonstrated broadband coupling operations with coupling losses of 2.4 dB at a wavelength of 1550 nm and a 0.5-dB spectrum bandwidth of more than 220 nm with TE-polarization light. [11]- [13] However, in this demonstration, the minimum coupling loss of the TM polarization was 1 dB larger than that of the TE polarization. Reducing the PDL as much as possible remains an important problem.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The device fabricated using electron-beam (EB) lithography demonstrated broadband coupling operations with coupling losses of 2.4 dB at a wavelength of 1550 nm and a 0.5-dB spectrum bandwidth of more than 220 nm with TE-polarization light. [11]- [13] However, in this demonstration, the minimum coupling loss of the TM polarization was 1 dB larger than that of the TE polarization. Reducing the PDL as much as possible remains an important problem.…”
Section: Introductionmentioning
confidence: 55%
“…The elephant coupler is composed of two sections: a VCW and an SSC [ Fig. 1(a)] [11]. The VCW section bends light through a right angle towards the surface of a chip, and the SSC enlarges the optical profile of the Si waveguide to match that of the optical fiber.…”
Section: Device Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the same authors also demonstrated the possibility to obtain light coupling between silicon vertical couplers and high numerical aperture fibers (5 μm MFD) [44,45]. Unlike their previous works, this time the Si nano-tapers were designed to show an exponential tapering profile, with the waveguide width decreasing from 430 to 50 nm over a 6 μm length, while the 90°waveguide bending was obtained by means of argon ion (Ar ) implantation (7 × 10 15 ions∕cm 2 ).…”
Section: Vertical End-fire Couplersmentioning
confidence: 99%
“…So far, a variety of effective coupling approaches have been demonstrated, [5] including end-fire coupling, [6][7][8][9][10][11] grating coupling, [12][13][14][15][16][17][18] and fiber-taper-assisted adiabatic coupling. [19][20][21][22][23][24] While they have been successfully applied with high efficiency and broad bandwidth, [8,24] high flexibility and large alignment tolerance remain challenging. To overcome these limitations, recently, photonic wire bonding based on adiabatic coupling method is proposed.…”
Section: Introductionmentioning
confidence: 99%